FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM BANK UMUM KONVENSIONAL LQ-45 DI BURSA EFEK INDONESIA - Koorniaharta, Dean Sanuya Hafizan; Marsudi, Almatius Setya (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
Bank companies manage corpoRate funding, one of which is by investing. Investments are carried out in the hope of obtaining stock Returns. This study examines the effect of Net Interest Margin, Capital Adequacy Ratio, Operating Income, Operational Expenses, and Bank Indonesia Reference Interest Rate on stock Returns in Indonesian banking companies. The sampling technique used was Purposive Sampling method, the sample obtained was 5 companies in the banking sector registered in LQ-45. Linear regression test is used to see the behavior of each variable. Data obtained as many as 200 out of 5 banking sector companies listed on LQ45 on the Indonesia Stock Exchange. The scope of research time is in the quarterly period of 2010 to 2019. The results show that the BI Reference Rate, Capital Adequacy Ratio and Operating Expenses, Operational Income, have no significant effect on bank stock Returns. On the other hand, Net Interest Margin has a significant effect on bank stock Returns.